Computer-Assisted Technique for Surgical Tooth Extraction - Hosamuddin Hamza (International Journal of Dentistry)
Introduction. Surgical tooth extraction is a common procedure in dentistry. However, numerous extraction cases show a high level of difficulty in practice. This difficulty is usually related to inadequate visualization, improper instrumentation, or other factors related to the targeted tooth (e.g., ankyloses or presence of bony undercut). Methods. In this work, the author presents a new technique for surgical tooth extraction based on 3D imaging, computer planning, and a new concept of computer-assisted manufacturing. Results. The outcome of this work is a surgical guide made by 3D printing of plastics and CNC of metals (hybrid outcome). In addition, the conventional surgical cutting tools (surgical burs) are modified with a number of stoppers adjusted to avoid any excessive drilling that could harm bone or other vital structures. Conclusion. The present outcome could provide a minimally invasive technique to overcome the routine complications facing dental surgeons in surgical extraction procedures.